Postcollisional evolution features of the intracontinental structures formed by overthrusting - Parphenuk Olga I. (Общество с ограниченной ответственностью «Георесурсы», 2018)
The investigation of intracontinental collision structures is conducted based on the complex model of the thermal and mechanical evolution of overthrusting process for the rheologically layered lithosphere, which includes brittle upper crust, the lower crust and lithospheric upper mantle with different effective viscosity values. Finite element models with Lagrangian approach were used for the problem simulation. It was shown that thermal evolution of continental orogens essentially results from the geometry and topography due to thrusting and postcollision stage. This work concentrates on the thermal parameters influence on the evolution of collision zones aimed to the study of possibility of granite melt formation. calculations for mean continental initial temperature distribution lead to the conclusion of possibility of granite melt formation for the case of “wet” granite solidus. The horizon of temperatures higher than “wet” granite solidus appears at the level of 30-40 km, moving upward to the depth 15-20 km at postcollision stage. The early postcollision evolution shows some heat flow increase due to the thickening of the upper crust with maximum heat generation rate. Further history leads to the stable heat flow values because additional loading redistribution resulting from the denudation of surface uplift and corresponding sedimentation is small due to the local erosion in our model. It was shown that surface heat losses after the termination of horizontal shortening depend to a greater extent on radiogenic heat generation rather than thermal conductivity value in the upper crust.
Keywords: collision; overthrusting; evolution; heat generation; heat flow value; thermal conductivity; rheology; temperature; solidus